2013
DOI: 10.2147/ijn.s43945
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen and fibrin based micro and nano scaffolds incorporated with drugs, proteins, cells and genes for therapeutic biomedical applications

Abstract: Over the past two decades, many types of natural and synthetic polymer-based micro-and nanocarriers, with exciting properties and applications, have been developed for application in various types of tissue regeneration, including bone, cartilage, nerve, blood vessels, and skin. The development of suitable polymers scaffold designs to aid the repair of specific cell types have created diverse and important potentials in tissue restoration. Fibrinogen (Fbg)-and fibrin (Fbn)-based micro-and nanostructures can pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 198 publications
(224 reference statements)
0
32
0
Order By: Relevance
“… 70 Some of the researches have shown that purified fibrin scaffolds cause less expression of collagen Type II and aggreacan compared with alginate. 13 17 54 In another study, alginate showed better stimulation of chondrogenesis in bone marrow derived MSCs when compared to fibrin. 58 Evidence show that chondrogenesis is recognized by increase in expression and accumulation of collagen Type II and aggreacan genes compared to collagen Type I and sox9.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“… 70 Some of the researches have shown that purified fibrin scaffolds cause less expression of collagen Type II and aggreacan compared with alginate. 13 17 54 In another study, alginate showed better stimulation of chondrogenesis in bone marrow derived MSCs when compared to fibrin. 58 Evidence show that chondrogenesis is recognized by increase in expression and accumulation of collagen Type II and aggreacan genes compared to collagen Type I and sox9.…”
Section: Discussionmentioning
confidence: 95%
“…Combination of fibrinogen clot and thrombin can induce binding, migration and growth of various types of cells such as chondrocytes, fibroblasts, smooth muscle cells and keratinocytes. 13 …”
Section: Introductionmentioning
confidence: 99%
“…We have used fibrin for the scaffold, as this is one of the major components of the extracellular matrix and is an attractive candidate for skin regeneration application (Rajangam & An, 2013). We selected fibrin due to suitable interactions with skin cells, a crucial property that promotes the wound healing process (Gsib, Egles, & Bencherif, 2017), abundance, versatility, biological relevance (Peterson et al, 2014), and cell encapsulation (Cummings, Gawlitta, Nerem, & Stegemann, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Both fibrinogen and fibrin are highly biocompatible, biodegradable, and non-immunogenic. In addition, its fibrous network can induce cell attachment and proliferation [179]. However, due to its weak and fragile nature of fibrin, to create robust and stable bioprinted 3D constructs from fibrin bioinks alone is challenging.…”
Section: Spatial Control Of Hydrogelsmentioning
confidence: 99%